Perancangan Media Pembelajaran E-Learning Sebagai Sarana Penunjang Proses Pembelajaran Di Smkn 1 Ampek Angkek Canduang - Fahrul Razi (Jurnal Sistem Informasi (JUSIN), 2022)
far, all learning processes in schools are still conventional, in other words that the teaching and learning process between students and teachers can only be done on condition that a meeting occurs between students and teachers. teacher in the classroom. One of the teaching methods that are currently being developed is e-learning. E-learning can help teachers distribute their teaching materials without having to be in class using the internet. This can maximize learning time in a limited class. In making this elearning using PHP which is used to create web pages and MySQL as a database where data is stored. The results obtained by e-learning can be applied and implemented to help teachers and students in schools in facilitating the teaching and learning process.